MUSLIMS, MINORITIES, AND THE MEDIA discourses on islam in the west. - De Rooij, Laurens ([S.l.] : ROUTLEDGE, 2023)
Inspired by overtly negative coverage by the Western mainstream press of Muslims in particular, and minorities in general, this book asks: Why are negative narratives and depictions of Muslims and other minorities so hard to change? News reports about Islam and Muslims commonly relate stories that discuss terrorism, violence or other unwelcome or irrational behaviour, or the lack of integration and compatibility of Muslims and Islam with Western values and society. Yet there is little research done on how studies on media reports about minorities seemingly fail to improve the situation. Combining empirical research with a structural analysis of the media industry, this volume presents evidence for the maligned representation of minorities by media corporations, analysing why negative narratives persist and outlining how these can be effectively transformed. It is an outstanding resource for students and scholars of media, religion, culture, sociology, and Islamic studies, and is also of benefit for journalists, media representatives, and activists looking to effect change for minority representation in the media industry specifically or in society at large.
Keywords: Islam -- Press coverage -- Western countries; Muslims -- Press coverage -- Western countries; Journalism -- Objectivity -- Western countries; Journalistic ethics -- Western countries; Minorities -- Press coverage; SOCIAL SCIENCE / Media Studies; RELIGION / Religion, Politics & State